2016
DOI: 10.1039/c6cc00984k
|View full text |Cite
|
Sign up to set email alerts
|

An unprecedented single platform via cross-linking of zeolite and MOFs

Abstract: The unprecedented ternary nanocomposites have been synthesized as a single platform via cross-linking of two nanoporous materials, MOFs and Pt nanoparticle (NP) loaded zeolite. The heterojunction of the novel nanocomposites is anticipated to work as a chemical platform for size selective catalytic hydrogenation or deuteration of small molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…This action might mention that electrostatic interaction is not the signi cant way to control the adsorption capacity of MOF-74 and ZSM-12@MOF-74 to cationic dye. Based on structure of MB dye and MOF-74, π − π stacking interaction as another force controlled the removal of MB on core@shell and MOF-74 [9]. The highest percentage of destruction was obtained (47.55% degradation and 80.37% removal) using ZSM-12@MOF-74 compared to those of MOF-74 (36.15% degradation) and zeolite ZSM-12 (18.35% degradation) at pH = 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This action might mention that electrostatic interaction is not the signi cant way to control the adsorption capacity of MOF-74 and ZSM-12@MOF-74 to cationic dye. Based on structure of MB dye and MOF-74, π − π stacking interaction as another force controlled the removal of MB on core@shell and MOF-74 [9]. The highest percentage of destruction was obtained (47.55% degradation and 80.37% removal) using ZSM-12@MOF-74 compared to those of MOF-74 (36.15% degradation) and zeolite ZSM-12 (18.35% degradation) at pH = 9.…”
Section: Resultsmentioning
confidence: 99%
“…The integration of MOF and zeolite into composite particles is envisaged to produce useful hybrid nanoporous where inorganic zeolite and organic MOF components transmit the advantages of high thermal, mechanical and structural stability of zeolites and speci c functionality and high exibility of MOFs [6]. There are a few reports on zeolite@MOF composites [7][8][9][10]. Recently, we reported synthesis of Zeolite Y @ MIL-53 (Al) core@shell [11], with modifying of zeolite Y surface with COOH groups.…”
Section: Introductionmentioning
confidence: 99%
“…The COOH functionalization procedure was adopted from a method reported previously with slight modification. 32 Prior to surface modification, the fine zeolite powder was heated and degassed under vacuum at 350 °C for 3 h to remove any preadsorbed humidity. About 7.5 g of succinic anhydride and 18 mL of APTES were dissolved in 100 mL of DMF, then the solution was stirred at room temperature for 25 min.…”
Section: Methodsmentioning
confidence: 99%
“…The composites exhibited bifunctional properties for cascade reactions. In a study by Lim et al, 32 the composites of Pt nanoparticles, NaY, and MOF-5 with core−shell structure were developed, and their H 2 adsorption behaviors were evaluated. The authors reported surface modification of zeolite with carboxylate prior to the synthesis of composites.…”
Section: Introductionmentioning
confidence: 99%
“…AlO(OH) and MOF share common characteristics of high surface affinity and tunable morphological and structural features such as shape, specific surface area, and pore/particle size but differ in thermal/mechanical stability and structural flexibility. The conjunction of MOF and AlO(OH) into composite materials is expected to produce useful hybrid materials where inorganic boehmite and organic MOF components transmit the advantages of high thermal, mechanical, and structural stability of AlO(OH) and specific functionality and high flexibility of MOFs such as MOFs with zeolites [26][27][28][29][30][31] and SiO 2 . [32] Herein, we proposed a novel strategy to prepare one new kind of well-defined MOF-based hybrid material by post-synthetic method.…”
Section: Introductionmentioning
confidence: 99%